The suggestion of the tv advertisement (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The suggestive peculiarities of advertising texts are analysed, the verbal and non-verbal means with suggestive meaning are found out, the mechanism of their influence on consumer is explained.
Keywords: suggestion; suggestive qualities; verbal means; non-verbal means; intonational peculiarities; imperative mood verbs